Mepolizumab: a new drug in asthma armamentorium - Choubey, Satyadeo; Ahuja, Kunal (International Journal of Basic & Clinical Pharmacology, 2016)
Bronchial asthma is a syndrome characterized by airflow obstruction that varies markedly, both spontaneously and with treatment. The current therapy for asthma includes either inhaled corticosteroids alone or in combinations with inhaled bronchodilators with other controller options being theophyllines, leukotriene antagonists and systemic corticosteroids. In step V of Global Initiative for Asthma (GINA) management guidelines Anti Ig E, Omalizumab is recommended in selected patients when everything fails. But still some unmet need is felt in the form of refractory asthma. Mepolizumab, an IL-5 antagonist has been developed in this regard and has been approved by FDA on Nov 4, 2015 followed by European commission on Dec 02, 2015 in view of good results based on clinical trials conducted by GlaxoSmithKline a multi-centre, open-label long-term safety study of 100 milligram (mg) mepolizumab administered subcutaneously (SC) every 4 weeks for 12 months in addition to standard of care in subjects who have severe, refractory asthma and a history of eosinophilic inflammation. This article covers the review of mepolizumab with its advantages in refractory bronchial asthma.